The Function of Language at Medan Train Station: Linguistic Landscape Study - Pasaribu, Gumarpi; Salmiah, Maryati; Junaidi (International Journal Linguistics of Sumatra and Malay, 2024)
This study explores the language functions of the linguistic landscape at the Medan train station, focusing on its symbolic and informational roles. Using a qualitative descriptive approach through observation, interviews, and documentation techniques, the research highlights the distinct characteristics of the linguistic landscape in this location. The findings reveal a dominance of monolingual Indonesian, which facilitates easy comprehension of billboards and signage for the majority of the population. Informational functions are well-developed, effectively serving to guide and assist users in navigating the station. Additionally, the inclusion of logos, such as the PT KAI logo, emphasizes the credibility and official nature of the messages conveyed. However, the research also identifies a significant underutilization of the symbolic function in the linguistic landscape, with limited representation of local cultural or linguistic elements. This gap is influenced by the public's mindset and a lack of attention to the potential of linguistic landscapes as tools for cultural preservation and identity expression. The study contributes to a deeper understanding of language usage patterns in public spaces and underscores the need for greater integration of symbolic elements, such as traditional scripts and multilingual signage, to enrich the cultural representation and literacy of the community. These findings hold implications for improving the design and functionality of billboards at the Medan train station, ensuring they serve both practical and cultural purposes for diverse users.